Rancang Bangun Sistem Penyaring Debu Cyclone pada Pirolisis Biomassa - Asep Iswanto; Sugeng Priyanto; Sopiyan Sopiyan; Lukman Arhami (Lembaga Intelektual Muda Maluku, 2024)
The purpose of the design of a cyclone dust filter system for biomass pyrolysis is as an alternative to improve the work yield of the biomass pyrolysis process. The cyclone functions as a filter for char and dust with gas produced after the pyrolysis process in the reactor tube, before being forwarded to the condenser and motor. The results of data analysis show that the biomass pyrolysis testing process with the addition of a cyclone dust filter system, the conclusion obtained is that with the addition of this cyclone dust filter system, the results of the biomass pyrolysis process obtained are even better, because the gas that is still mixed with char and dust will be filtered in this process. The test results using wood shavings, corn cobs, and rice husks also showed improvements compared to without using a cyclone dust filter system